Localization of 25-hydroxyvitamin D3 1 alpha-hydroxylase and 24-hydroxylase along the rat nephron. - Kawashima, H (1981)
Defined nephron segments were microdissected from the kidney of vitamin D-deficient rats, normal rats, and normal rats treated with 1 alpha, 25-dihydroxyvitamin D3 [1 alpha, 25-(OH)2D3]. Tubule segments were incubated with 3H]labeled 25-hydroxyvitamin D3 and the rates of production of 3H]labeled 1 alpha, 25-(OH)2D3 and 24,25-dihydroxyvitamin D3 [24,25-(OH)2D3] were determined. Nephron segments tested include the glomerulus, proximal convoluted tubules (PCT), proximal straight tubules (PST), medullary and cortical thick ascending limbs of Henle's loop, distal tubules, and collecting tubules. Production of 1 alpha, 25-(OH)2D3 was detected only in PCT of vitamin D-deficient rats (mean +/- SEM, 0.70 +/- 0.05 fmol/mm per hr); the value decreased to 0.11 +/- 0.05 after parathyroidectomy. By contrast, significant 24,25-(OH)2D3 production occurred in PCT of normal rats (0.23 +/- 0.05 fmol/mm per hr). After administration of 1 alpha, 25-(OH)2D3 to normal rats, the rate of production of 24,25-(OH)2D3 in PCT increased to 0.64 +/- 0.06 fmol/mm per hr and also became apparent in PST (1.07 +/- 0.21). The rates of production of 1 alpha, 25-(OH)2D3 and 24,25-(OH)2D3 in these nephron segments were linear with tubule length over a wide range of lengths per incubation and with the incubation time. The results define the localization of 25-hydroxyvitamin D3 1 alpha-hydroxylase and 24-hydroxylase along the rat nephron: PCT is capable of producing both 1 alpha, 25-(OH)2D3 and 24,25-(OH)2D3 and PST can produce 24,25-(OH)2D3. the use of defined nephron segments may be useful for study of the distribution and regulation of 25-hydroxyvitamin D3 hydroxylases in the kidney.